POTENSI TIGA ISOLAT BAKTERI INDIGEN DARI KABUPATEN SIAK PROVINSI RIAU DALAM MENDEGRADASI NAFTALENA - R. Novianty; B. Antika; . Saryono; A. Awaluddin; N. W. Pratiwi (Jurnal Kimia (Journal of Chemistry), 2020)
Naphthalene is a group of Polycyclic Aromatic Hydrocarbons (PAHs) which is carcinogenic when presents in the environment. The purpose of this study was to determine the growth response and test the effectiveness of three isolates of indigen bacteria from the Joint Operation Agency area of ??PT. Siak Bumi Pusako-Pertamina Hulu (BOB BSP-PHE) in degrading naphthalene. The three isolates were tested in a Minimum Media (MM) liquid containing naphthalene with a final concentration of 0.2 mM and was incubated for 7 days. Optical Density (OD) and the degradation ability were analyzed using a UV-Vis spectrophotometer. The results showed that Pseudomonas sp. LBKURCC149 was able to grow in media containing naphthalene. Naphthalene is used as the only source of carbon and is able to degrade naphthalene by 21.98%. Keywords: biodegradation, indigenous, naphthalene, Pseudomonas sp.